Indigenous identity in South Asia: making claims in the colonial Chittagong hill tracts - Chowdhury, Tamina M. (© 2016 Taylor and Francis., 2018)
This book was published by Taylor and Francis, 2016[© 2017 Tamina M. Chowdhury. ] and the definitive version is available at: https://doi.org/10.4324/9781315561967. The publisher's website is at: https://www.taylorfrancis.com/books/9781317202936.